Rapid and Simple Detection of Viable Foodborne Pathogen Staphylococcus aureus - Liu, Caiyan; Shi, Chao; Li, Mengzhe; Wang, Mengyuan; Ma, Cuiping; Wang, Zonghua (Frontiers in Chemistry, 2019)
Staphylococcus aureus (S. aureus) contamination in food safety has become a worldwide health problem. In this work, we utilized RNA one-step detection of denaturation bubble-mediated Strand Exchange Amplification (SEA) method to realize the detection of viable foodborne pathogen S. aureus. A pair of S. aureus specific primers were designed for the SEA reaction by targeting hypervariable V2 region of 16S rDNA and the amplification reaction was finished about 1 h. The results of amplification reaction could be observed by the naked eyes with a significant color change from light yellow to red to realize the colorimetric detection of S. aureus. Therefore, there was only needing an isothermal water bath, which was very popular for areas with limited resources. In real sample testing, although the SEA detection was so time-saving compared with the traditional plating method, the SEA method showed great consistency with the traditional plating method. In view of the above-described advantages, we provided a simple, rapid and equipment-free detection method, which had a great potential on ponit-of-care testing (POCT) application. Our method reported here will also provide a POCT detection platform for other food-borne pathogens in food, even pathogenic bacteria from other fields.